Recreational Potential and Regional Differentiation of Tourism Industry Enterprises in the EU - CHUMAKOVA, Olga V. (Journal of Environmental Management and Tourism, 2019)
The article notes that the development of recreation and tourism at the present stage of development of society is given more attention, because this type of activity for many countries and regions is strategic, is in the sphere of priority development of many territories, including the European Union. The authors note that tourist and recreational activities are considered to be one of the most profitable in the world. The importance of identifying the components of the tourist and recreational potential of the territory and their interrelations, as well as the degree of influence on the effectiveness of tourism. The novelty of the work is the calculation of the adapted methodology for determining the recreational potential and its identification with the concept of tourist potential. The authors show that the existing methods determine only homogeneous parameters of tourism development or a single industry. In the proposed method of calculation, it is possible to use diverse indicators for homogeneous integral calculation. The prospect of the research development for the EU countries is the application of the obtained methodology in order to facilitate the calculation of joint recreational potential for the border regions.